1986
DOI: 10.1002/pola.1986.080240727
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of semiconducting aromatic polyquinonediimines

Abstract: synopsisA new class of poly-conjugated polymers has been obtained by condensation of anthraquinones with aromatic diamines in plyphosphoric acid. The polymers are black, intractable powders. Toward obtaining tractable materials, the effect of monomer structure on polymer tractability has been studied. Copolymerizations were also carried out to "soften" these materials. Electrical conductivities in the semiconducting range, 10 10 (ohm crn1-I were observed. Doping with iodine showed small increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…1(b). This buckling angle is the same as that of the unsubstituted diimine 1c, 13 and is 8Њ larger than that of the 1,4-methoxy derivative 1d. 10 The peri-OH groups in 1a would have a role in retaining molecular planarity due to the intramolecular hydrogen bonds rather than exerting steric hindrance, leading to molecular buckling.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…1(b). This buckling angle is the same as that of the unsubstituted diimine 1c, 13 and is 8Њ larger than that of the 1,4-methoxy derivative 1d. 10 The peri-OH groups in 1a would have a role in retaining molecular planarity due to the intramolecular hydrogen bonds rather than exerting steric hindrance, leading to molecular buckling.…”
Section: Resultsmentioning
confidence: 72%
“…General methods 1 H and 13 C NMR spectra were recorded at 500 MHz in CDCl 3 unless specified otherwise and are reported in ppm units with TMS as internal standard. J values are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The IR spectra were recorded on a IR-470 Shimadzu spectrophotometer using the KBr pellet technique. 1 H-NMR spec-tra were run on a Varian EM-390 90-MHz NMR spectrometer at room temperature in dimethylsulfoxide (DMSO) using tetramethylsilane as the internal reference. The UV-visible spectra were scanned on a Shimadzu 2110 PC scanning spectrophotometer in dimethylformamide (DMF).…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…It is well known that electronic mobility in conjugated organic polymers is greatly enhanced along a polymer molecule with conjugated bonds, A great variety of such materials have received attention. [1][2][3][4][5] These materials are prepared by polymerization of simple monomers that are able to form a network of highly delocalized electrons. Moreover, conjugated organic polymers have gained increasing interest in recent years as electrically conducting polymers [e.g., poly(p-phenylene), polypyrrole, polythiophene, and others].…”
Section: Introductionmentioning
confidence: 99%
“…The diimine model compound DAQ was synthesized in crystalline form. 20 X-ray single crystal structure determination revealed that the centralfused ring system was not planar, but buckled 268 to a \butterfly" configuration. A similar butterfly configuration has been reported for N,N 0 -dicyanoanthraquinone-9,10-diimine, with the cyano groups in the syn configuration.…”
mentioning
confidence: 99%